1981
DOI: 10.1038/bjc.1981.154
|View full text |Cite
|
Sign up to set email alerts
|

Cell subpopulations dispersed from solid tumours and separated by centrifugal elutriation

Abstract: Summary.-The degree of non-neoplastic host-cell infiltration was assessed in 3 in vivo-in vitro tumour models commonly used in radiobiological studies: EMT6/Ro mammary carcinoma, 9L/Ro tumour and KHT sarcoma. While the 2 former tumour models have been shown to be moderately to highly immunogenic when grown s.c., the KHT sarcoma is apparently non-immunogenic. Using differential staining on single-cell suspensions from enzymatically dissociated solid tumours, all 3 tumour types were found to contain large propor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…A possible explanation for the lack of a detectable change is offered by Kallinowski et al (1989), who postulated that a decrease in oxygen consumption by tumour cells may be concealed by an up to 70-fold elevation in oxygen consumption by immune cells. Approximately 40% of cells from dissociated KHT-C tumours have been reported to be immune cells, primarily macrophages (Siemann et al, 1981). Alternatively, this observation may be due to the absence of anaesthetics in the current study, use of which has been reported to influence tissue pH e and pO 2 (Buelke-Sam et al, 1978;Kerger et al, 1997).…”
Section: Discussioncontrasting
confidence: 40%
“…A possible explanation for the lack of a detectable change is offered by Kallinowski et al (1989), who postulated that a decrease in oxygen consumption by tumour cells may be concealed by an up to 70-fold elevation in oxygen consumption by immune cells. Approximately 40% of cells from dissociated KHT-C tumours have been reported to be immune cells, primarily macrophages (Siemann et al, 1981). Alternatively, this observation may be due to the absence of anaesthetics in the current study, use of which has been reported to influence tissue pH e and pO 2 (Buelke-Sam et al, 1978;Kerger et al, 1997).…”
Section: Discussioncontrasting
confidence: 40%
“…The regimen-dependent induction of inflammatory responses following PDT could also account for the failure of other groups to detect an effect of Foscan (meta-tetrahydroxyphenylchlorin)-PDT of orthotopic rat liver tumours on liver tumours present outside the treatment field (van Duijnhoven et al, 2003). In addition, NK cell activation of DCs in anti-tumour immunity appears to depend upon tumour expression of NKG2D ligands (Adam et al, 2005), or expression of costimulatory molecules such as CD70, CD80 or CD86 (Kelly et al, 2002); EMT6 tumours are immunogenic (Siemann et al, 1981) respond well to PDT (Korbelik and Dougherty, 1999) and may be more susceptible to immune-mediated control. PDT is likely to be less effective at stimulating systemic anti-tumour immune responses against less immunogenic tumours such as those used in other PDT studies of systemic immunity (van Duijnhoven et al, 2003).…”
Section: à2mentioning
confidence: 99%
“…There has been much recent interest in the possibility of growing spheroids directly from disaggregated clinical tumour material. Suspensions prepared from solid tumours generally contain a considerable population of normal host cells including macrophages, endothelial cells, lymphocytes and granulocytes (Siemann et al, 1981). The proportions will vary between tumour types, but investigation of two different sublines of the EMT6 mouse tumour have showed that -40% of the total cellular composition consists of macrophages (Stewart & Beetham, 1978;Siemann et al, 1981 (Twentyman & Watson, 1977).…”
mentioning
confidence: 99%
“…Suspensions prepared from solid tumours generally contain a considerable population of normal host cells including macrophages, endothelial cells, lymphocytes and granulocytes (Siemann et al, 1981). The proportions will vary between tumour types, but investigation of two different sublines of the EMT6 mouse tumour have showed that -40% of the total cellular composition consists of macrophages (Stewart & Beetham, 1978;Siemann et al, 1981 (Twentyman & Watson, 1977). A suspension prepared from the solid tumour contains -40% host cells and these may be separated from tumour cells by a selective adherence technique (Twentyman & Watson, 1977).…”
mentioning
confidence: 99%